Mendamaikan Sains dan Agama: Mempertimbangkan Teori Harun Nasution - Aprison, Wedra (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
The development of science in the Islamic universities requires strong philosophical,ontological, epistemological, and axiological base. The formulation of epistemologycan not be negotiable. From the thought of Harun Nasution, it can be said that “thesource of religion is revelation and the source of knowledge is God’s natural law calledthe sunatullah”. Both come from one source, namely Allah. So between the revelationand sunatullah can not be put into contradiction. Ayat al-kawniyah in the Quran hasencouraged the classic Islamic scholars to study and observe the natural surroundings.The implication of this theory is that any special methodology is not needed to developthe current science. Furthermore Harun said, “because Islam is a religion and culture,and the culture is more than religion, a different research method may not necessary thanthe commonly used.”